How Iron Technology Changed the Ancient World and Gave the Philistines a Military Edge - Muhly, James David (The Biblical archaeology review, 1982)
042 Modern historians divide the roughly 3,000 year-period beginning approximately 3200 B.C. into two major segments—the Bronze Age and the Iron Age. The Bronze Age I extends from about 3200 B.C. to 1200 B.C.a Thereafter it is the Iron Age.b This is some indication of the enormous importance (as well as the date […]